Release of acyclovir from polymeric nanofibers: comparing aqueous versus membrane-water interfaces kinetics - Costa, Tiago (2017)
We are very thankful to Labesfal Genericos, S.A. for kindly providing acyclovir. We also thank PARALAB for the SEM-EDS analysis and Sr. Azevedo for the X-ray analysis. This work was supported by the Portuguese Foundation for Science and Technology (FCT) in the framework of the Strategic Funding UID/FIS/04650/2013. Marlene Lúcio acknowledges the exploratory project funded by FCT with the reference IF/00498/2012